Assessment of medication adherence among patients with chronic diseases: a descriptive cross-sectional study - Mir, Shakeel Ahmad; Muzamil, Furqanah; Bhat, Mehraj UD Din; Amin, Abid; Shakeel, Danish (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Adherence is a key factor associated with effectiveness of all pharmacological therapies. Medication non-adherence is a significant barrier to achieve positive health outcomes especially for patients suffering from chronic diseases. Improving medication adherence is a public health priority and could reduce economic and health burdens. The aim of the present study was to assess medication adherence to some common chronic ailments. Methods: Pre-validated questionnaires were distributed among 300 patients suffering from chronic illnesses, by simple randomization out of which 240 patients returned completely filled questionnaires. The analysis was done by manual calculators, VassarStats, and SPSS V20. Results were calculated using univariate linear regression, with each patient’s adherence score as the dependent variable and each predictor as the independent variable. Results are expressed in frequencies and percentages. Results: In this study, 46.66% patients were males and 53.33% females. The mean age was 56.69 years ranging from 24 to 90 years.65.00% patients were uneducated.40.00% were taking one drug, 53.33% two to four drugs and 6.66% more than four drugs. 63.33% had low medication adherence, 35.00% medium and only 1.66% had high adherence. Compared to 14.28% men, 43.75% women were moderately adherent to medications. 41.02% uneducated patients had medium adherence as compared to 14.28% educated patients. 92.30% young patients had low adherence as compared to 53.25% in adults. 44.79% of patients receiving a single drug had medium adherence as compared to 25.00% in those receiving multiple drugs. Linear regression analysis demonstrated that the level of medication adherence was associated with patient gender, age, educational level, and number of prescribed drugs. Conclusions: There are many challenges in understanding the reasons for non-adherence. In this study medication adherence in chronic diseases was found suboptimal and associated with patient`s socio-demographic characteristics. Patient-tailored interventions are required to achieve sufficient adherence to therapeutic drug regimens.